Integrating music and nature: a scoping review of research on interventions involving both music- and nature-based strategies for mental health and wellbeing - Hand, Michelle D.; Ihara, Emily S.; Moore, Morgan; Shaw, Madison (Frontiers in Human Neuroscience, 2025)
IntroductionBoth music-related and nature-based therapeutic activities can enhance wellbeing, physical, social, emotional, and mental health, and recovery from posttraumatic stress. While music- and nature-based therapeutic approaches have been studied individually, research is limited on the holistic combination of music- and nature-based therapeutic interventions. Thus, a scoping review was conducted to chart primary research on the combined use of music- and nature-based therapeutic strategies and their effects on overall wellbeing, and within this scope, potentially on mental and behavioral health outcomes.MethodsIncluded were peer-reviewed articles reporting primary research findings on how (if at all) the combined use of both music and nature-based interventions impacted wellbeing and thus, mental and behavioral health. All studies had to be reported in English. Excluded were studies that did not involve both nature-based and music-related therapeutic activities, those not involving primary research, and articles without a clear discussion on potential impacts on wellbeing, mental, or behavioral health. After applying this inclusion and exclusion criteria, 884 potentially relevant peer-reviewed articles were identified, 23 of which were preliminarily screened in upon abstract and title review. After full text reading, eight of these articles were deemed eligible for the review and were thematically analyzed.ResultsFour themes were identified from the reviewed studies: (a) music- and nature-based activities yield benefits across various aspects of wellbeing, (b) multiple activities can be combined and adapted for diverse contexts and populations, (c) more research is needed on the combined therapeutic use of music and nature, and (d) choice and expression should be prioritized, which music and nature can facilitate. The primary focus of the reviewed studies was on how music-based interventions in outdoor or natural settings can impact multiple aspects of wellbeing, particularly emotional wellbeing, and with this, improved mood.DiscussionThe results suggest that combining music and nature-based therapeutic approaches can improve mental and behavioral health by enhancing multiple aspects of wellbeing. For example, music-making in natural settings can foster deep connections with nature and spiritual wellness. Implications for future research are provided, as further research is needed on the combined use of music- and nature-based therapeutic activities.